Serum Fibroblast Growth Factor 21 Level Is Associated with Aortic Stiffness in Patients on Maintenance Hemodialysis - Liang-Te Chiu; Chi-Di Hung; Lin Lin; Yu-Li Lin; Bang-Gee Hsu (International Journal of Hypertension)
Background. Fibroblast growth factor 21 (FGF-21) is a hormone that regulates glucose and lipid metabolism. High serum FGF-21 levels are associated with carotid atherosclerosis and coronary artery disease. This cross-sectional study aimed to assess the relationship between serum FGF-21 levels and carotid-femoral pulse wave velocity (cfPWV) in patients on maintenance hemodialysis (HD). Methods. Blood samples and baseline characteristics were collected from 130 HD patients. Serum FGF-21 concentrations were measured with an enzyme-linked immunosorbent assay kit. Aortic stiffness was defined as a carotid-femoral pulse wave velocity (cfPWV) of more than 10 m/s. Results. Of the 130 HD patients, aortic stiffness was diagnosed in 54 (41.5%). Serum FGF-21 levels were significantly higher in those with aortic stiffness than those without P<0.001. The FGF-21 level was independently associated with aortic stiffness (odds ratio (OR): 1.008; 95% CI: 1.003–1.012; P=0.001) after adjusting for diabetes mellitus, age, hypertension, C-reactive protein, and body weight in multivariable logistic regression analysis. Multivariable forward stepwise linear regression analysis also confirmed that the logarithmically transformed FGF-21 level (β = 3.245, 95% CI: 1.593–4.987, P<0.001) was an independent predictor of cfPWV values. The area under the receiver operating characteristic (ROC) curve predicting aortic stiffness by the serum FGF-21 level was 0.693 (95% CI: 0.606–0.771, P<0.001). Conclusions. Serum FGF-21 level positively correlates with cfPWV and is also an independent predictor of aortic stiffness in maintenance HD patients.